2015
DOI: 10.3346/jkms.2015.30.12.1856
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicity of Nonsteroidal Anti-inflammatory Eye Drops against Human Corneal Epithelial Cells in Vitro

Abstract: This study investigated the toxicity of commercial non-steroid anti-inflammatory drug (NSAID) eye solutions against corneal epithelial cells in vitro. The biologic effects of 1/100-, 1/50-, and 1/10-diluted bromfenac sodium, pranoprofen, diclofenac sodium, and the fluorometholone on corneal epithelial cells were evaluated after 1-, 4-, 12-, and 24-hr of exposure compared to corneal epithelial cell treated with balanced salt solution as control. Cellular metabolic activity, cellular damage, and morphology were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 25 publications
0
24
0
5
Order By: Relevance
“…NSAIDs are widely used after various ocular surgeries, expecting anti-inflammatory and analgesic effects via inhibition of the enzymes cyclooxygenase 1/2. On the other hand, the toxicity of NSAIDs against corneal re-epithelialization has been investigated both in vitro [ 4 ] and in vivo [ 8 ]. Çerman et al [ 9 ] suggested that proinflammatory cytokines directly secreted from damaged epithelial cells may be released into the stroma and consequently trigger the migration of inflammatory cells to the affected stroma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSAIDs are widely used after various ocular surgeries, expecting anti-inflammatory and analgesic effects via inhibition of the enzymes cyclooxygenase 1/2. On the other hand, the toxicity of NSAIDs against corneal re-epithelialization has been investigated both in vitro [ 4 ] and in vivo [ 8 ]. Çerman et al [ 9 ] suggested that proinflammatory cytokines directly secreted from damaged epithelial cells may be released into the stroma and consequently trigger the migration of inflammatory cells to the affected stroma.…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs inhibit cyclooxygenases and decrease prostaglandin production; their use for corneal wound healing is a matter of debate. Postoperative use of topical NSAIDs promotes faster wound healing [ 3 ]; however, Lee et al [ 4 ] investigated the toxicity of NSAID eye solutions against corneal epithelial cells in vitro. Asai et al [ 5 ] reported 3 cases of corneal melting caused by bromfenac sodium used to treat surface and postoperative inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…27 Bromfenac is usually used to prevent macular edema and inflammation after cataract and complex ocular surgeries, [27][28][29] which is less toxic toward corneal epithelial cells. 30 Our study intended to explore whether bromfenac has the potential to prevent the excessive wound healing that takes place after the pterygium surgeries.…”
Section: Methodsmentioning
confidence: 99%
“…33 To assess the antifibrotic effects of bromfenac on TGF-b1-induced cells, the cultured HPFs and HConFs were divided into the following groups and treated for 48 hours: the control group; the TGF-b1 group, in which the cells were exposed to 20 ng/mL TGF-b1 (200-1; PeproTech, Rocky Hill, NJ, USA); the bromfenac group, in which the cells were treated with 90 lg/mL bromfenac (bromfenac active components were from Senju Pharmaceutical, Osaka, Japan); the TGF-b1 þ bromfenac group, in which the cells were treated with 20 ng/mL TGF-b1 plus 90 lg/mL bromfenac. For the dose-effect relationship study, HPFs and HConFs were treated with three concentrations of bromfenac (30,60, and 90 lg/mL) for 48 hours. For the inhibitors studies, 200 nM wortmannin (#S2758; Selleck, Houston, TX, USA) (PI3K inhibitor) and 20 lM U0126 (#9903S; CST, Waltham, MA, USA) (MEK inhibitor) were added 2 hours before the TGF-b1 treatment, and the HPFs and HConFs were collected 48 hours after TGF-b1 treatment to evaluate the changes.…”
Section: Drug Treatments Of Cellsmentioning
confidence: 99%
“…Нестероидные противовоспалительные средства назначали, как правило, коротким курсом на 3-5 дней для купирования/уменьшения болевого синдрома и потенцирования мидриаза. Более длительное их применение представляется нецелесообразным из-за возможного подавления процессов заживления роговицы (вплоть до развития местных трофических нарушений) [18][19][20].…”
Section: материал и методыunclassified